31. MEDICATION ADHERENCE MANAGEMENT OF HYPERTENSIVE OUTPATIENTS AT TRADITIONAL MEDICINE HOSPITAL IN VINH PHUC IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: Hypertension is a chronic disease that requires adherence of the patients to prevent unwanted complications. This study aims to evaluate the Medication adherence management of hypertensive outpatients at Traditional Medicine Hospital in Vinh Phuc in 2022.Research method: This cross-sectional study (quantitative method) was conducted within 3 months (April-July/2022) at Traditional Medicine Hospital in Vinh Phuc. Quantitative data was collected by face-to-face interview for a convenient selected 200 hypertensive outpatients. Data was analyzed using SPSS ver 25.0.Findings: Regarding medication adherence management, 90% of patients were monitored for drug adherence when they had regular check-ups and were counseled on medication adherence. Regarding daily blood pressure, 11% of patients did not have their blood pressure measured by health workers at follow-up visits and up to 14.1% of patients were measured but were not recorded in the patient book. Regarding management of follow-up visits, the majority of hypertensive patients were reminded by health workers for visit and record the time in personal monitoring books (75.5%). Regarding lifestyle change, 47.5% of patients have not changed their lifestyle. Regarding information-education-communication, this activity was limited.Conclusion: Traditional Medicine Hospital in Vinh Phuc needs to strengthen counseling for outpatients on treatment adherence and follow-up visit. Further, hospital should enhance outpatient management through electronic medical records and follow-up appointments. Finally, it is necessary to mobilize family members to support hypertensive outpatients during treatment.
Keywords: Hypertension, outpatient patient management, treatment compliance, Traditional Medicine Hospital in Vinh Phuc.